Anthropogenic forcing increases the water‐use efficiency of African trees. (17th June 2016) - Wils, Tommy H. G.; Robertson, Iain; Woodborne, Stephan; Hall, Grant; Koprowski, Marcin; Eshetu, Zewdu
ABSTRACT: Rising atmospheric CO2 concentrations affect climate directly through radiative effects and indirectly by changing plant water‐use efficiency. Under global warming scenarios these widely reported changes will have a substantial impact on future bush encroachment, crop yields, river flow and climate feedbacks. Tree‐ring intrinsic water‐use efficiency (iWUE) records for Africa show a 24.6% increase over the 20th century. As high iWUE can partly counterbalance projected decreases in regional precipitation, this research has important implications for those involved in water resource management and highlights the need for climate models to take physiological forcing into account.